Interactive Educational Media with Gamification for Introducing Traditional Costumes to Students - Taufik Bima Maulana; Muhammad Ikhsan Thohir; Dhita Diana Dewi (Komunitas Dosen Indonesia, 2025)
Introducing local culture at an early age is crucial for fostering national identity, yet cultural education in Indonesian elementary schools often relies on conventional, one-way methods that fail to engage digitally native students. Prior studies using TikTok in education have been limited to passive video formats without interactive features, creating a gap for immersive, gamified approaches. This study develops and evaluates an innovative interactive educational medium using TikTok filters with gamification and Augmented Reality (AR) to introduce Indonesian traditional costumes to elementary students. The ADDIE model (Analysis, Design, Development, Implementation, Evaluation) was applied, and the media was tested with fourth-grade students at SDN 2 Parakanlima. Developed via the Effect House platform, the media presents a visual quiz where students answer through head gestures, promoting active participation. Evaluation through observation, interviews, questionnaires, and basic quantitative metrics showed a 35% increase in engagement, a 28% improvement in comprehension scores, and 92% of students reporting higher motivation. Teachers rated usability at 4.7/5 and emphasized its contextual relevance. This study concludes that TikTok filter-based educational media with gamification and AR is an effective, engaging, and accessible solution for cultural learning in the digital era. Its novelty lies in integrating AR, gamification, and a widely used social platform into a single tool for cultural education, offering a replicable model for other subjects and contexts.